Relationship between risk factors for impaired bone health and HR-pQCT in young adults with type 1 diabetes - Sochett, Etienne B.; Dominicis, Mary; Vali, Reza; Shammas, Amer; Elia, Yesmino; Moineddin, Rahim; Mahmud, Farid; Assor, Esther; Furman, Michelle; Boyd, Steve K.; Lenherr-Taube, Nina (Frontiers in Endocrinology, 2023)
OBJECTIVE In type 1 diabetes, risk factors associated with impaired bone health contribute to increased risk of fracture. The aim of this study was to: (1) compare the high resolution peripheral quantitative computed tomography (HR-pQCT) parameters of young adults with type 1 diabetes with those of healthy controls, (2) identify sex differences, and (3) evaluate the association between diabetes and bone health risk factors, with HR-pQCT. METHODS This is a cross-sectional study in young Canadian adults with childhood onset type 1 diabetes. Z-scores were generated for HR-pQCT parameters using a large healthy control database. Diet, physical activity, BMI, hemoglobin A1C (A1C) and bone health measures were evaluated, and associations were analyzed using multivariate regression analysis. RESULTS Eighty-eight participants (age 21±2.2 years; 40 males, 48 females, diabetes duration 13.9±3.4 years) with type 1 diabetes were studied. Low trabecular thickness and elevated cortical geometry parameters were found suggesting impaired bone quality. There were no sex differences. Significant associations were found: Vitamin D (25(OH)D) with trabecular parameters with possible synergy with A1C, parathyroid hormone with cortical parameters, BMI with cortical bone and failure load, and diabetes duration with trabecular area. CONCLUSIONS Our data suggests impairment of bone health as assessed by HR-pQCT in young adults with type 1 diabetes. Modifiable risk factors were associated with trabecular and cortical parameters. These findings imply that correction of vitamin D deficiency, prevention and treatment of secondary hyperparathyroidism and optimization of metabolic control may reduce incident fractures.